Endometrial stromal cell miR-19b-3p release is reduced during decidualization implying a role in decidual-trophoblast cross-talk - Menkhorst, Ellen; So, Teresa; Rainczuk, Kate; Barton, Siena; Zhou, Wei; Edgell, Tracey; Dimitriadis, Evdokia (Frontiers in Endocrinology, 2023)
A healthy pregnancy requires successful blastocyst implantation into an adequately prepared or ‘receptive’ endometrium. To prepare for embryo implantation and pregnancy, uterine endometrial stromal fibroblast (hESF) decidualize in response to progesterone to become decidual cells. microRNAs (miRs) are critical regulators of cellular function that can be released by a donor cell to influence the physiological state of recipient cells. We aimed to determine how decidualization affects hESF miR release using a microRNA microarray and validated the expression and function of one decidualization regulated mir, miR-19b-3p, previously shown to be associated with recurrent pregnancy loss. From our miR screen we found that miR release by hESF was significantly reduced following in vitro decidualization. In situ hybridization localized miR-19b-3p to epithelial and stromal cells in the endometrium and qPCR identified that miR-19b-3p was significantly elevated in the cycling endometrium of patients with a history of early pregnancy loss compared to normally fertile controls. Functionally, overexpression of miR-19b-3p significantly reduced HTR8/Svneo trophoblast proliferation and increased HOXA9 expression. Overall, our data demonstrate that decidualization represses miR release and that decidual released miR-19b-3p likely regulators trophoblast function.